PERANCANGAN SISTEM OPEN SOURCE UNTUK PENETRATION TESTING PADA WEBSITE PORTAL AKADEMIK - Alif Al Farizi; Yusuf Ramadhan Nasution; Muhamad Alda (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract:One technique for locating security flaws in information systems is penetration testing. This research aims to design and implement an open-source system that integrates several penetration testing tools to assess the security of the PortalSIA UINSU website. The tools used include Paramspider, Dalfox, Cyberfox, Sqlmap, and Penblood. The system is designed to perform parameter scanning, exploitation, and automatic reporting of test results in a structured manner. The results show that out of five tested URLs, most did not reveal significant vulnerabilities, except for some connectivity issues during the SQL injection testing stage. This system can be utilized as a tool to efficiently detect and analyze potential vulnerabilities in target websites.  Keyword:Penetration Testing, Open Source, Website Security  Abstrak:Salah satuteknikuntukmenemukankelemahankeamanandalamsisteminformasiadalahpengujianpenetrasi. Penelitianinibertujuanuntukmerancang dan mengimplementasikansistemsumberterbuka yang mengintegrasikanbeberapaalatpengujianpenetrasiuntukmenilaikeamanan situs web PortalSIA UINSU. Alat yang digunakanmeliputiParamspider, Dalfox, Cyberfox, Sqlmap, dan Penblood. Sisteminidirancanguntukmelakukanpemindaian parameter, eksploitasi, dan pelaporanotomatishasilpengujiansecaraterstruktur. Hasil penelitianmenunjukkanbahwadari lima URL yang diuji, sebagianbesartidakmengungkapkankerentanan yang signifikan, kecualibeberapamasalahkonektivitasselamatahappengujianinjeksi SQL. Sisteminidapatdigunakansebagaialatuntukmendeteksi dan menganalisispotensikerentanansecaraefisien di situs web target.  Kata kunci:PengujianPenetrasi, Open Source, Keamanan Situs Web